THE AUTOMATIC TRAIN ROUTE SETTING SYSTEM AND POSSIBILITIES OF ITS OPTIMIZATION (Perner's Contacts, 2023)
The article deals with the optimalization of the Automatic Train Route Setting System's activity. First, readers are introduced to the original method, the proposal of a new generating method for the construction of train routes and outline their development. The possibilities of optimalization methods are suggest with the primary goal of the increase of the capacity by the maximization of the train travel fluency. The article introduces the readers with the use of the Automatic Train Route Setting System in the Czech Republic.
Keywords: Automatic Train Route Setting System; train route; time method; geographical method; last time point; initialization point; railway